2019
DOI: 10.1097/corr.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity Associated With Increased Risk of Deep Vein Thrombosis or Pulmonary Embolism After Hip and Knee Arthroplasty? A Large Database Study

Abstract: Cardiac Valve and Other Major Cardiothoracic Measure 12 Percent of PCI procedures with angiographic success and no death, myocardial infarction (MI), or emergent/salvage CABG Semi-Annual Calculation by RTI Measure Percent of ACE Demonstration cardiovascular procedure redos or revisions within six months X X X Annual Calculation by RTI Measure Inpatient Mortality Rate X X X X X X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 33 publications
5
80
3
3
Order By: Relevance
“…We note that although the outright proportion of obese patients is lower, the mean Table 1 SUMMARY OF BASELINE CHARACTERISTICS BMI was about 28kg/m 2 which is consistent with overweight patients. The increase of BMI was associated in several studies with an increased risk of PE, some authors proposing that the vascular inflammatory state being one of the predisposing factors or insulin resistance [8][9].…”
Section: Resultsmentioning
confidence: 99%
“…We note that although the outright proportion of obese patients is lower, the mean Table 1 SUMMARY OF BASELINE CHARACTERISTICS BMI was about 28kg/m 2 which is consistent with overweight patients. The increase of BMI was associated in several studies with an increased risk of PE, some authors proposing that the vascular inflammatory state being one of the predisposing factors or insulin resistance [8][9].…”
Section: Resultsmentioning
confidence: 99%
“…In a recently published study using Nationwide Inpatient Sample Database, Movahed et al 48 showed that obese patients have significantly higher incidence of PE as compared with non-obese patients. In another recent study in post-orthopaedic surgery patients, Sloan et al 49 showed that both overweight and obese patients had increased risk of PE. However, the risk of extremity venous thromboembolism was not elevated in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…They found the 30-day and 90-day risk of VTED to be lower for revision TKA than for primary TKA after controlling for age, race, gender, and medical comorbidities [ 16 ]. Of note, the data was geographically limited to one state, and smoking status, BMI, and operative time, previously cited risk factors for VTE, were not controlled for [ 26 – 28 ]. The lower VTED risk of revision TKA compared with primary TKA found in our study was not expected.…”
Section: Discussionmentioning
confidence: 99%